2023
DOI: 10.2174/1570180819666220610101055
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Protective Role of Rhodanese Enzyme against Cyanide, the Cytotoxic by-product of Amygdalin, in HDF and L929 Cell Lines

Abstract: Introduction: Amygdalin (AMG) is a plant-based agent that has many therapeutic applications. Metabolism of this herbal remedy may cause cytotoxicity in cells. Objective: In this study, the role of rhodanese (RH) enzyme against the cyanide of amygdalin has been investigated in human and mouse cell lines in vitro Method: : We analyzed the cytotoxicity, morphologic changes, apoptotic effects, and gene expression alterations resulting from treatment with AMG and AMG combined with RH (AMG-RH) in mouse fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Chloramphenicol dramatically decreased cell viability at increasing doses, as seen by the findings of the MTT cytotoxicity experiment. At the highest dose of 100 mg/kg body weight, cell viability in the tissues of the liver, kidney, and heart decreased by 39.02 percent, 43.04 percent, and 36.25 percent [15]. These findings show the chloramphenicol's dosedependent cytotoxicity, with higher doses significantly lowering cell viability in all organ tissues under study.…”
Section: Discussionmentioning
confidence: 66%
“…Chloramphenicol dramatically decreased cell viability at increasing doses, as seen by the findings of the MTT cytotoxicity experiment. At the highest dose of 100 mg/kg body weight, cell viability in the tissues of the liver, kidney, and heart decreased by 39.02 percent, 43.04 percent, and 36.25 percent [15]. These findings show the chloramphenicol's dosedependent cytotoxicity, with higher doses significantly lowering cell viability in all organ tissues under study.…”
Section: Discussionmentioning
confidence: 66%
“…Dental care has become more difficult to get as a direct consequence of their being less people utilizing adipose transplanted patients [48,49] . A recent study found that the majority of oral surgeons stop taking warfarin before conducting low-risk procedures on patients who have received adipose transplants [50][51][52][53] . This was the recommendation made by the researchers of the study.…”
Section: Discussionmentioning
confidence: 99%